Pengungkapan Penerapan Corporate Social Responsibility pada Hotel Aston Kuta - Kusnadewi, Kusnadewi; Dharma Suputra, Dewa Gede (E-Jurnal Akuntansi; Vol 31 No 7 (2021), 2021)
Nowadays, society and companies are increasing aware of the importance of environmental conservation of  activities, improvement of economic standards and social harmony. CSR is away to show the company’s concern for the environment and the suroounding community. Corporate Social Responsibility (CSR) activities, or also known as Social Activities or often called Sustainability Development, are not a disclosure of the behavior of an individual in a company but are a disclosure of corporate behavior that can increase social trust in the company. Corporate Social Responsibility (CSR) activities for a hotel do not directly increase company profits, but by carrying out these activities in the environment and in the surrounding community, it will improve the company's image in the eyes of the public. There are various kinds of activities that can be categorized as part of CSR, from the promotion and marketing of social activities, philanthropic activities (charity), voluntary social/ community work. Keywords: Corporate Social Responsibility (CSR); Disclosure of Corporate Behavior; Improve The Company's Image In The Eyes of The Public; Various Kinds Of  CSR.